The enhanced anti-obesity effect and reduced gastric mucosa irritation of capsaicin-loaded nanoemulsions. Issue 5 (26th April 2017) - Lu, Muwen; Cao, Yong; Ho, Chi-Tang; Huang, Qingrong
Abstract : Organogel-derived capsaicin nanoemulsions can inhibit diet-induced hepatic steatosis and reduce epididymal adipocyte size and tissue mass. Abstract : Capsaicin (CAP), the major active component of chili peppers, is known to have thermogenic and weight-loss potential. The aim of this study was to investigate the anti-obesity effects of capsaicin-loaded nanoemulsions (C-NE) on male Sprague Dawley (SD) rats treated with a high-fat diet (HFD). The food grade C-NE was prepared using capsaicin, medium chain triacylglycerols (MCT) (Neobee 1053), sucrose stearate S-370, Tween 80 and distilled water with an emulsion droplet size of 168 nm and a capsaicin loading of 80.4 mg mL −1 . Results showed that C-NE effectively decreased body weight gain and hypercholesterolemia induced by HFD in a dose-dependent manner. Histological evaluations of the liver and adipose tissue confirmed that C-NE had significant effects on inhibiting diet-induced hepatic steatosis, reducing epididymal adipocyte size and tissue mass. A gastric mucosa irritation test demonstrated that C-NE was effective in alleviating the gastric inflammation caused by free unformulated CAP crystals.